2007
DOI: 10.1111/j.1745-7270.2007.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transformation Efficiency of <italic>piggyBac</italic> Transposon among Three Different Silkworm <italic>Bombyx mori</italic> Strains

Abstract: The transformation rate of three different strains of silkworm Bombyx mori was compared after the introduction of enhanced green fluorescence protein (EGFP)-encoding genes into the silkworm eggs by microinjection of a mixture of piggyBac vector and helper plasmid containing a transposase-encoding sequence. Although there were no significant differences among the three strains in the percentages of fertile moths in microinjected eggs (P=0.1258), the percentages of G(0) transformed moths in fertile moths and inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…For example, the successful germline transformation of silkworm, using a piggyBac transposon‐derived vector, is of particular relevance for new sericulture approaches (Prudhomme & Couble, 2002). Although there have been many reports on the successful germline transformation of silkworm mediated by a piggyBac‐derived vector (Tamura et al , 2000; Tomita et al , 2003; Royer et al , 2005; Dai et al , 2007; Zhong et al , 2007; Zhao et al , 2010), all the studies were conducted using non‐diapausing eggs from polyvoltine silkworm strains, except for the study by Inoue et al (2005), in which diapause strains identified as Nd‐s D were used. The main reason for this discrepancy is that non‐diapausing eggs from polyvoltine strains are capable of continuous development before and after microinjections under normal environment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the successful germline transformation of silkworm, using a piggyBac transposon‐derived vector, is of particular relevance for new sericulture approaches (Prudhomme & Couble, 2002). Although there have been many reports on the successful germline transformation of silkworm mediated by a piggyBac‐derived vector (Tamura et al , 2000; Tomita et al , 2003; Royer et al , 2005; Dai et al , 2007; Zhong et al , 2007; Zhao et al , 2010), all the studies were conducted using non‐diapausing eggs from polyvoltine silkworm strains, except for the study by Inoue et al (2005), in which diapause strains identified as Nd‐s D were used. The main reason for this discrepancy is that non‐diapausing eggs from polyvoltine strains are capable of continuous development before and after microinjections under normal environment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the microinjection and screening of transgenic silkworms were carried out according to Zhong et al [12]. Eggs of silkworms were collected and microinjected within 8 h after eggs being laid at the syncytial pre-blastoderm stage.…”
Section: Microinjection and Screening Of Transgenic Silkwormsmentioning
confidence: 99%
“…BmN cells derived from the ovarian tissue of Bombyx mori were maintained at the Shanghai Institutes for Biological Sciences (Shanghai, China). Microinjection and screening of transgenic silkworms Microinjection and screening of transgenic silkworms were done as described previously [22]. Approximately 15 -20 nl of a 1:0.5 mixture of the transposon (donor) plasmids and transposase (helper) plasmids (total DNA concentration 0.3 mg/ml) were microinjected into each egg.…”
Section: Silkworm Strainsmentioning
confidence: 99%